An evaluation of grouper and snapper fisheries management policy in Saleh Bay, Indonesia. Issue 1 (April 2021) - Efendi, D S; Adrianto, L; Yonvitner,; Wardiatno, Y
Abstract: In the policy context, managing grouper and snapper fisheries resources for sustainability is a big challenge due to the complexity of small-scale fisheries in Saleh Bay. This study implemented two analytical methods: length-based analysis and ecosystem approach to fisheries assessment to evaluate the performance of the implementation of the grouper and snapper fisheries management in Saleh Bay. The results showed after policy implementation, the mean length of species has been slightly larger and three species already reached the spawning potential ratio (SPR) target reference point. However, two of the 11 species regulated had SPR values below the limit reference point, which indicated that these species are currently fished at unsustainable levels. Overall, the assessment of fishery risk index indicated the risk status of this fisheries in the category of moderate risk, 1.185, in which two dimensions need to be improved: socio-economy and habitat. Therefore, this study highlighted leverage points to achieve 'good' performance level, such as socialization program intensively, enforcing regulation to provincial regulation, strengthening the surveillance and law enforcement of destructive fishing practices, empowerment of local institutions by co-management, and rehabilitation of coral reef ecosystems.